Tinjauan Hukum Pendidikan Profesi Kedokteran Gigi Dalam Pelaksanaan Pelayanan Kesehatan - Kyagus Badius Sani (Magister Ilmu Hukum - Universitas Hang Tuah, 2022)
A doctor/dentist in practice must meet formal education standards in terms of academic education and professional education recognized by law. Dental professional education in providing medical services at the Teaching Dental and Oral Hospital (RSGMP) is carried out by Ko-AS students (young dentists) under the supervision of the dentist in charge of services (DPJP). The delegation of authority from the DPJP to Ko-As students is carried out using a clinical delegation letter as the legal basis for providing medical services even though the competence and authority are not yet possessed by the students. Regulation of the Minister of Health number 2052/Menkes/Per/X/2011 article 24 paragraph 1 concerning Practice License and Implementation of Medical Practice explains that doctors and dentists who work in teaching hospitals and health service facilities network, in carrying out educational tasks can provide guidance/ implementation/supervision of medical/dentistry education participants to provide medical services to patients.This can lead to legal consequences from the implementation of dental professional education in administrative, criminal and civil ways. This research is a normative and socio legal legal research with a conceptual approach. Aims to find out the legal basis for the Koas to carry out dental medical procedures under the supervision of the DPJP. The results, conclusions and suggestions related to the problem are discussed.